Comparative experiment of steel bar corrosion at concrete construction joints - Huang, Guohua; Wu, Binzhong; Shen, Yin; Wang, Li; Li, Guoping (Frontiers in Materials, 2022)
Construction joint may lead to increased corrosion of reinforcement in concrete and become a durability weakness of concrete structure. This study presents a comparative electrochemically accelerated corrosion tests to assess the effect of construction joints on chloride-induced corrosion of reinforcing steel in concrete. The comparative experiment studied four types of rebars commonly used in marine and offshore concrete structures; two environmental conditions, namely the marine environment and the offshore tidal environment; and two forms of construction joints. Experimental results showed that except for epoxy-coated steel bars, the most severe corrosion of experimental steel bars in concrete specimens all occurred at the joints, while the corrosion in non-joint sections of steel bars was relatively uniform and less. The rust amounts of rebars at the joint sections were greater than that of the non-joint sections and the average ratio was 1.76. In addition, the corrosion of rebars at the joints under wet–dry cycle condition was more severe than under immersion conditions.